Desain Kurikulum Pendidikan Agama Kristen Bagi Kelas Katekisasi Anggota Jemaat GMIT Pasca Konversi Agama - Windy Daud; Ningsih Diliyanti Benu (Jurnal Shanan, 2023)
Religious conversion is a phenomenon that often occurs today. It is where people move from old religions and beliefs to a new religions and beliefs. This can happen because of a matter of faith, marriage, following parents, and so on. This religious conversion also often occurs within the GMIT community. GMIT as a church that is called to reveal light in the world needs to realize one of its missions, namely teaching. The purpose of this writing is to design a Christian Religious Education curriculum for catechism class members of the GMIT congregation after religious conversion. The research method used in this paper is descriptive qualitative. The curriculum design that was contributed could be used as a reference in learning that is more effective, efficient and maximal. The results of this study indicate that the design of the Christian Religious Education’s curriculum donated can be utilized in catechism classes for post religious conversion of GMIT congregation members, and fulfil church duties and services in the realm of teaching.